2020
DOI: 10.1159/000507583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Growth Restriction on Cerebral Regional Oxygen Saturation in Preterm and Term Neonates during Immediate Postnatal Transition

Abstract: Background: Intrauterine growth restriction (IUGR) is associated with adverse perinatal outcome. Affected fetuses commonly display typical blood flow redistribution towards the brain ("brain sparing"). Accordingly, increased cerebral oxygen saturation has been observed in IUGR neonates within the first days of life. Aim: The aim of our study was to assess cerebral oxygenation behavior during immediate neonatal transition in IUGR infants. Methods: This is a retrospective single-center observational cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Postnatally, neonates who experienced IUGR have persistent vasodilation of cerebral vasculature ( 94 ). This can result in higher ScO 2 values by NIRS likely due to a combination of increased cerebral oxygen delivery and a decreased cerebral tissue oxygen consumption ( 95 ). The key factor in using this technique is to not rely soley on the single timepoint measurement; rather, a trend in CPR is required to determine where on the trajectory a fetus is in regard to CA.…”
Section: Cerebral Blood Flow In Vulnerable Fetal and Neonatal Populationsmentioning
confidence: 99%
“…Postnatally, neonates who experienced IUGR have persistent vasodilation of cerebral vasculature ( 94 ). This can result in higher ScO 2 values by NIRS likely due to a combination of increased cerebral oxygen delivery and a decreased cerebral tissue oxygen consumption ( 95 ). The key factor in using this technique is to not rely soley on the single timepoint measurement; rather, a trend in CPR is required to determine where on the trajectory a fetus is in regard to CA.…”
Section: Cerebral Blood Flow In Vulnerable Fetal and Neonatal Populationsmentioning
confidence: 99%
“…Our finding of higher cerebral rSO2 values in IUGR term neonates is in accordance with cerebral oxygenation data in IUGR preterm infants where higher values have been consistently reported in the first days after birth 26 , 27 . Recently, Baik-Schneditz et al also showed significantly higher cerebral rSO2 values and lower rates of oxygen extraction during the first 15 min after birth in IUGR preterm and term neonates when compared with AGA peers 28 . In regard to cerebral oxygen extraction, we found that IUGR infants had a decreased cerebral FTOE after birth.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with Baik-Schneditz's research that an intrauterine growth restriction group did show significantly higher cSO 2 values. 32 The abnormal high cerebral oxygen levels might cause oxidative stress and cell damage in oxygensensitive organs, such as the developing brain. 32 Therefore, anesthesiologists should pay attention to the risk of neonatal cerebral oxygen abnormalities when managing anesthesia in a pregnant mother with comorbidities, such as PIH.…”
Section: Discussionmentioning
confidence: 99%
“…32 The abnormal high cerebral oxygen levels might cause oxidative stress and cell damage in oxygensensitive organs, such as the developing brain. 32 Therefore, anesthesiologists should pay attention to the risk of neonatal cerebral oxygen abnormalities when managing anesthesia in a pregnant mother with comorbidities, such as PIH. In contrast, decreases in BP were shown to poorly correlate with decreases in relative cSO 2 levels, which were comparable to the findings of 2 previous studies.…”
Section: Discussionmentioning
confidence: 99%